McDowell e a indelimitação do conceitual. Um retorno ao pensamento objetivo de Hegel? - Bordignon, Michela (Revista Eletrônica Estudos Hegelianos, 2018)
In this article, I will try to answer the following question: is McDowell's notion of the unboundedness of the conceptual a return to Hegelian idea of objective thought? The article will be divided into two parts: 1) in the first part, I will examine some points of convergence of Hegel’s idea of objective thought with McDowell’s notion of the unboundedness of the conceptual; 2) in the second part, I will show that the lack of justification of McDowell’s understandings of the logical space of concepts prevents to equate its unboundedness with the absolute character that Hegel attributes to the notion of logical form.While Hegel’s analysis of the constitution of conceptual space is completely justified and mediated in itself, McDowell's idea of the combination of spontaneity with receptivity and hence of the unity of subjectivity and objectivity is taken as way out of aporiai of empiricism and idealism.